2014
DOI: 10.7287/peerj.preprints.681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of autotrophic and mixotrophic regimen Chlorella pyrenoidosa cells in various wastes water for its biochemical composition and biomass production

Abstract: The present study investigates the possibility of integrating an existing industrial large scale biomass production with the treatment of waste water in which a mixture of organic and inorganic rich pollutants was used as a medium. This study suggests that the replacement of a defined medium with a complete mixotrophic medium gives a significant statistical difference in terms of growth parameters i.e. biomass production and specific growth rate.The green microalga C. pyrenoidosa was cultivated under different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…On the other hand, the dry weight contents at different concentrations of crude oil were classified into three categories, which showed a significant difference, so that the control concentration had the lowest value and concentrations of 1-5% crude oil shows the highest amount (Table 4). Dhull et al (2014) found that by increasing the concentration of carbon in the medium, the biomass production rate increases in some microalgae species, which is consistent with the results of this study.…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, the dry weight contents at different concentrations of crude oil were classified into three categories, which showed a significant difference, so that the control concentration had the lowest value and concentrations of 1-5% crude oil shows the highest amount (Table 4). Dhull et al (2014) found that by increasing the concentration of carbon in the medium, the biomass production rate increases in some microalgae species, which is consistent with the results of this study.…”
Section: Resultssupporting
confidence: 92%
“…In the mixotrophic cultures, the content of protein in C. kessleri decreased from 54.3% to 34.9%, whereas that of carbohydrate increased from 12.6% to 28.2% with the increase of glucose concentrations from 2 to 15 g L −1 . In agreement with the present study, the same changes of protein and carbohydrate contents in C. pyrenoidosa were observed by Dhull et al ., who found that the contents of protein and carbohydrate were 65.0%, 20.3% and 39.3%, 54.0%, when C. pyrenoidosa grew in the photoautotrophic and mixotrophic cultures, respectively. Moreover, the content of lipids in C. kessleri increased firstly from 25.0% to 32.7% with increasing glucose concentrations from 2 to 6 g L −1 , and then maintained at c .32.0% when the glucose concentrations were > 6 g L −1 .…”
Section: Resultsmentioning
confidence: 91%
“…The cellular concentration for C. pyrenoidosa was determined by withdrawing 5 ml of microalgae suspension throughout the experiment (8 days) via the test tube. In this way, optical density measurements were carried out using a FEMTO 700 PLUS spectrophotometer, whose reading wavelength was 686nm, and the following equation was used Growth rate (wet biomass) = (observed optical density / 0.0563) (R 2 = 0.9989) (DHULL et al, 2014).…”
Section: Determination Of Cellular Concentrationmentioning
confidence: 99%